Wage Effects of Mobility, Unemployment Benefits and Benefit Financing - Hans Lindblad (Sveriges Riksbank, 2000)
This paper studies how wages and employment are affected by unemployment insurance when there is endogenous labor mobility. In a simple model with symmetric sectors, it is shown that introducing labor mobility reduces the wage level, and thereby also unemployment. It is also shown that an increased benefit level has an ambiguous effect on the wage level, contrary to the standard result in the literature. The finding in the literature that an increase in the fraction of unemployment costs borne by the own sector reduces the wage level is shown to hold when labor is mobile as well. Another result is that wage costs in general are higher when unemployment benefits are financed through pay-roll taxes compared to the case when they are financed through income taxes. Thus in general, the tax equivalence result in the literature does not hold.
Keywords: E50; 330; Labor mobility; Unemployment benefits